2015
DOI: 10.1128/iai.02888-14
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Host Proteins Involved in Rickettsial Invasion of Tick Cells

Abstract: Tick-borne spotted fever group (SFG) Rickettsia species are obligate intracellular bacteria capable of infecting both vertebrate and invertebrate host cells, an essential process for subsequent bacterial survival in distinct hosts. The host cell signaling molecules involved in the uptake of Rickettsia into mammalian and Drosophila cells have been identified; however, invasion into tick cells is understudied. Considering the movement of SFG Rickettsia between vertebrate and invertebrate hosts, the hypothesis is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…Together, the data suggest that R. parkeri strains deficient in functional RickA or Sca2 display conserved phenotypes in arthropod and mammalian cells in vitro . Observed deficiencies in ABM were expected, as the host protein complexes utilized for actin-based motility, e.g., Arp2/3 complex, are functional in tick cells ( 20 , 21 ). Interestingly, compared to wild-type R. parkeri , decreased late-phase actin polymerization was observed for R. parkeri rickA :: tn , coinciding with reduced cell-to-cell spread.…”
Section: Discussionmentioning
confidence: 99%
“…Together, the data suggest that R. parkeri strains deficient in functional RickA or Sca2 display conserved phenotypes in arthropod and mammalian cells in vitro . Observed deficiencies in ABM were expected, as the host protein complexes utilized for actin-based motility, e.g., Arp2/3 complex, are functional in tick cells ( 20 , 21 ). Interestingly, compared to wild-type R. parkeri , decreased late-phase actin polymerization was observed for R. parkeri rickA :: tn , coinciding with reduced cell-to-cell spread.…”
Section: Discussionmentioning
confidence: 99%
“…More knowledge on these specific interactions could perhaps be used in order to interfere with cell to cell spread of specific bacteria. The protein complex Arp2/3 is a major component in the regulation of the actin cytoskeleton of most eukaryotic cells [142] and various studies - both in mammalian and tick cell lines - have shown this complex is recruited by SFG Rickettsia in order to enter their host’s cells through endocytosis [134, 142144]. Studies using varying concentrations of an Arp2/3 complex inhibitor and transcriptional profiles of infected versus uninfected Dermacentor variabilis cells established its importance for R. montanensis invasion [142, 144].…”
Section: Rickettsiamentioning
confidence: 99%
“…The protein complex Arp2/3 is a major component in the regulation of the actin cytoskeleton of most eukaryotic cells [142] and various studies - both in mammalian and tick cell lines - have shown this complex is recruited by SFG Rickettsia in order to enter their host’s cells through endocytosis [134, 142144]. Studies using varying concentrations of an Arp2/3 complex inhibitor and transcriptional profiles of infected versus uninfected Dermacentor variabilis cells established its importance for R. montanensis invasion [142, 144]. Similar results have been shown for R. monacensis , R. conorii and R. rickettsii by examining rickettsial proteins that interact with the Arp2/3 complex, such as RickA [143, 145, 146].…”
Section: Rickettsiamentioning
confidence: 99%
See 2 more Smart Citations